An Index-Based Approach to Assessing Recalcitrance and Soil Carbon Sequestration Potential of Engineered Black Carbons (Biochars) - Harvey, Omar R; Kuo, Li-Jung; Zimmerman, Andrew R; Louchouarn, Patrick; Amonette, James E; Herbert, Bruce E (Environmental science & technology, 2012)
The ability of engineered black carbons (or biochars) to resist abiotic and, or biotic degradation (herein referred to as recalcitrance) is crucial to their successful deployment as a soil carbon sequestration strategy. A new recalcitrance index, the R 50, for assessing biochar quality for carbon sequestration is proposed. The R 50 is based on the relative thermal stability of a given biochar to that of graphite and was developed and evaluated with a variety of biochars (n = 59), and soot-like black carbons. Comparison of R 50, with biochar physicochemical properties and biochar-C mineralization revealed the existence of a quantifiable relationship between R 50 and biochar recalcitrance. As presented here, the R 50 is immediately applicable to pre-land application screening of biochars into Class A (R 50 ≥ 0.70), Class B (0.50 ≤ R 50 < 0.70) or Class C (R 50 < 0.50) recalcitrance/carbon sequestration classes. Class A and Class C biochars would have carbon sequestration potential comparable to soot/graphite and uncharred plant biomass, respectively, whereas Class B biochars would have intermediate carbon sequestration potential. We believe that the coupling of the R 50 , to an index-based degradation, and an economic model could provide a suitable framework in which to comprehensively assess soil carbon sequestration in biochars.